Extended use or re-use of single-use surgical masks and filtering facepiece respirators during COVID-19: a rapid systematic review - Toomey, E; Conway, Y; Burton, C; Smith, S; Smalle, M; Chan, X; Adisesh, A; Tanveer, S; Ross, L; Thomson, I; Devane, D; Greenhalgh, T (Cambridge University Press, 2020)
BACKGROUND: Shortages of personal protective equipment during the COVID-19 pandemic has led to the extended use or re-use of single-use respirators and surgical masks by frontline healthcare workers. The evidence base underpinning such practices warrants examination. OBJECTIVES: To synthesise current guidance and systematic review evidence on extended use, re-use, or reprocessing of single-use surgical masks or filtering facepiece respirators. DATA SOURCES: World Health Organization, European Centre for Disease Prevention and Control, the US Centers for Disease Control and Prevention, and Public Health England websites to identify guidance. Medline, Pubmed, Epistemonikos, Cochrane Database and preprint servers for systematic reviews. METHODS:Two reviewers conducted screening and data extraction. Quality of included systematic reviews was appraised using AMSTAR-2. Findings were narratively synthesised. RESULTS: Six guidance documents were identified. Levels of detail and consistency across documents varied. Four high-quality systematic reviews were included: three focused on reprocessing (decontamination) of N95 respirators, one on reprocessing of surgical masks. Vaporised hydrogen peroxide and ultraviolet germicidal irradiation were highlighted as the most promising reprocessing methods, but evidence on the relative efficacy and safety of different methods was limited. We found no well-established methods for reprocessing respirators at scale. CONCLUSIONS: There is limited evidence on the impact of extended use and re-use of surgical masks and respirators and gaps and inconsistencies exist in current guidance. Where extended use or re-use is being practiced, healthcare organisations should ensure that policies and systems are in place to ensure these practices are carried out safely and in line with available guidance.